A putative exosporium lipoprotein GBAA0190 of Bacillus anthracis as a potential anthrax vaccine candidate - Jun Ho Jeon; Yeon Hee Kim; Kyung Ae Kim; Yu-Ri Kim; Sun-Je Woo; Ye Jin Choi; Gi-eun Rhie (BMC Immunology, 2021)
Abstract Background Bacillus ancthracis causes cutaneous, pulmonary, or gastrointestinal forms of anthrax. B. anthracis is a pathogenic bacterium that is potentially to be used in bioterrorism because it can be produced in the form of spores. Currently, protective antigen (PA)-based vaccines are being used for the prevention of anthrax, but it is necessary to develop more safe and effective vaccines due to their prolonged immunization schedules and adverse reactions. Methods We selected the lipoprotein GBAA0190, a potent inducer of host immune response, present in anthrax spores as a novel potential vaccine candidate. Then, we evaluated its immune-stimulating activity in the bone marrow-derived macrophages (BMDMs) using enzyme-linked immunosorbent assay (ELISA) and Western blot analysis. Protective efficacy of GBAA0190 was evaluated in the guinea pig (GP) model. Results The recombinant GBAA0190 (r0190) protein induced the expression of various inflammatory cytokines including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and macrophage inflammatory protein-1α (MIP-1α) in the BMDMs. These immune responses were mediated through toll-like receptor 1/2 via activation of mitogen-activated protein (MAP) kinase and Nuclear factor-κB (NF-κB) pathways. We demonstrated that not only immunization of r0190 alone, but also combined immunization with r0190 and recombinant PA showed significant protective efficacy against B. anthracis spore challenges in the GP model. Conclusions Our results suggest that r0190 may be a potential target for anthrax vaccine.